'True biographies of nations?' : the cultural journeys of dictionaries of national biography - Fox, Karen (ANU.Lives series in biography., 2019)
Dictionaries of national biography are a long-established and significant genre of biographical and historical writing, existing in many forms across the globe. This book brings together practitioners from around the English-speaking world to reflect on national biographical dictionary projects' recent cultural journeys, and the challenges presented to them by such developments as the transition to a digital environment, a new alertness to the need to represent diversity, and the rise of transnationalism. Exploring their paths forward, the chapters of this book collectively make a powerful argument for the continued value and importance of large-scale collaborative biographical dictionary research.